Cognitive brakes in interference resolution: A mouse-tracking and EEG co-registration study. (December 2020) - Tafuro, Alessandra; Vallesi, Antonino; Ambrosini, Ettore
Abstract: Cognitive control is particularly challenged when it is necessary to resolve interference and correct our behavior on-the-fly. To do this, it is necessary to inhibit the ongoing wrong action and reprogram a new motor plan as appropriate for the current task. This ability requires a complex interaction between cognitive and motor control. Here, we aimed at shedding light on this interplay. To do this, we administered a spatial version of the Stroop task comprising blocks with different Proportion Congruency (PC) manipulations (i.e., manipulating the percentage of congruent trials at 25%, 50% or 75%), to elicit different cognitive control demands. Moreover, we used two techniques with high-temporal resolution, as we simultaneously recorded EEG and mouse trajectories, that can be considered the real-time kinematic correlates of the ongoing cognitive processing. Specifically, we analyzed the Event Related Potentials (ERPs) locked to the peak deceleration time, which marks the suppression of ongoing erroneous trajectories, and we estimated their neural sources. We found three PC-dependent ERP components engaging distinct neural regions, which showed a reduction of the Stroop effect for low-PC blocks. By using a novel co-registration of mouse-trajectories and EEG, we suggest that the observed components may reflect different mechanisms engaged by reactive cognitive control to resolve the interference, including the suppression of an ongoing but no longer appropriate response, the selection of the new motor plan and its actual updating.